THE IMPACT OF DIVERSIFICATION, SIZE, GROWTH, LOAN, DEPOSIT, EQUITY, AND LLP ON BANK RISK DURING THE COVID-19 PANDEMIC - Putri, Mia Ivana Gunawan; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to obtain empirical evidence about the effect of revenue diversification, firm size, firm growth, loan, deposit, equity, and loan loss provision on bank risk during the COVID-19 pandemic in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 period. The number of samples was 29 banking companies selected by purposive sampling method. The data were processed and analyzed using multiple linear regression analysis techniques through EViews 9. The results showed that revenue diversification, firm growth, deposit, and loan loss provision had a significant positive effect on bank risk. Firm size and loan have a significant negative on bank risk. Equity has no significant effect on bank risk.